Exploring the Catrina, an autochthonous cattle breed of the Azores, for a comparative analysis of methane emissions with Holstein-Friesian dairy cows - Azevedo, Ana Rita; Lopes, Maria Susana; Borba, Alfredo; da Câmara Machado, Artur; Mendonça, Duarte (Frontiers in Animal Science, 2024)
Introduction The struggle against climate change in agriculture requires an increased understanding of greenhouse gas emissions, mainly from cattle farming. Through precise and accessible methods to monitor the methane (CH4) emissions of these animals, it is possible to assess the influence of several factors.Therefore, this study evaluates CH4 emissions from Catrina cattle, an autochthonous breed from the Azores, and Holstein-Friesian cattle, aiming to assess the potential environmental impact and sustainability of this native breed. Materials and methods The present study was performed on a total of 15 dry cows, seven Catrina and eight Holstein-Friesian, housed by breed, in groups of five animals. The laser methane detector was used to assess the repeatability and reproducibility of CH4 values, including peaks and respiration. Descriptive statistics for raw data, CH4 breath and peaks, and the amount of CH4 emitted per day and year were calculated. Results From the Catrina breed, the average of CH4 emissions were 37.04 ± 40.09 ppm x m for raw data, 33.15 ± 28.59 ppm x m for CH4 breath, and 218.65 ± 67.13 ppm x m for CH4 peaks. From the Holstein-Friesian, the values obtained were 65.62 ± 87.11 ppm x m, 57.57 ± 52.59 ppm x m, and 514.19 ± 266.02 ppm x m, respectively. Linear mixed models, the Chisquare method and ANOVA, which showed a significant breed effect (p < 0.001) across all datasets, with trends favoring higher emissions in Holstein-Friesian were also applied. Similarly, Pearson correlation analyses yielded consistent trends, however, with no statistical significance (p > 0.05). Discussion and conclusion The findings underscore the importance of preserving cultural and genetic heritage while addressing climate change and environmental challenges. Furthermore, the study highlights the adaptive capacity of autochthonous breeds to their local environments, suggesting their role in sustainable systems. However, methane emissions will be influenced by several factors, besides breed variable, so this study emphasizes the need to integrate the assessment of the microbiome, which depends on the composition of the diet, genetic characteristics, and other aspects, for the development of methane mitigation strategies, with the inclusion of native breeds in sustainable resource management and climate adaptation efforts.